Long-term Export Financing - Counterpurchase as a Creative Instrument of Collateral for Export Credits - Systematic Illustration of an Export Business to Bulgaria with a Parallel Counterpurchase - Kessler, Lovrenc (My University, 2005)
The following thesis scrutinises the function of counterpurchase within the framework of long-term export financing and examines whether counterpurchase can serve as an instrument of collateral for export credits. For this reason, an Export Business of DaimlerChrysler to Bulgaria with a parallel counterpurchase is systematically illustrated. After covering the risk problem and the institutions participating in export finance counterpurchase is presented and its function as an instrument of collateral is explained. In order to determine the theoretical applicability of counterpurchase as an instrument of collateral for export credits, two different businesses of DaimlerChrysler are researched. The first concerns an export business with the Republic of Bulgaria, the second deals with a private Bulgarian company. The research result shows that for the Republic of Bulgaria both in the short and long term counterpurchase as collateral is not a relevant means to finance export credits. However, as far as private Bulgarian companies are concerned, there is a trend that in the short and mid term the relevance of counterpurchase as collateral will continue.
Keywords: Long-term Export Financing; Counterpurchase; Collateral; Export Business; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|